Do Facebook and Google Care about Journalism? Mapping the Relationship between Affordances of GNI and FJP Tools and Journalistic Norms - Papa, Venetia; Kouros, Theodoros (My University, 2023)
This study engages in a sociotechnical analysis of Facebook and Google to understand the material means by which these corporations strive to engage journalists vis-à-vis their business models. Through affordance theory, we argue that interfaces of technological artifacts are manifestations of their implicit politics and ideology, given that affordances entail normative claims about what users should do. Our study draws from Google News Initiative and Facebook Journalism Project to explore: how the affordances of FJP and GNI tools allow particular behaviors and encourage certain journalistic norms to emerge? We analyzed nine journalist-oriented tools from FJP and GNI, by performing a discursive interface analysis. Findings indicate that FJP and GNI tools affordances can encourage four distinct journalistic norms: (1) successful journalism should circulate widely on platforms, (2) successful journalism should be aware of the ways competition is measured in FJP and GNI, (3) successful journalism should attract loyal readership as defined by platforms and (4) successful journalism should make money through platforms. We argue that FJP and GNI tools affordances can facilitate a form of platform schooling which, in addition to journalism schools and work environments, can might dictate what is and what is not “successful journalism.”.
Keywords: Affordances; Facebook; Google; measurable journalism; norm-making; platformization